Media Framing and Peace Advocacy in Mainstream Coverage of the Herder-Farmer Conflicts in Nigeria (Journal of Management and Social Sciences, 2025)
The protracted conflict between farmers and herders in Nigeria, characterised by recurring violence, displacement, and social unrest, remains a significant challenge to national cohesion. This study investigates media framing and peace advocacy in mainstream coverage of the herder-farmer conflicts in Nigeria, using the framing theory as its analytical framework. A triangulated research approach was adopted, combining content analysis of 150 online reports from three purposively selected newspapers (Punch, Daily Trust, and Vanguard) with a survey of 251 members of the Nigerian Union of Journalists in Kwara State. Data were collected using coding sheets and structured questionnaires and analysed using descriptive statistics. The findings reveal that conflict reporting is predominantly framed using panic and fear-inducing narratives, with limited emphasis on peace-oriented frames such as solution or awareness frames. Although journalists expressed awareness of the influence of framing on peacebuilding efforts, their ability to reflect this awareness in practice is constrained by institutional and structural challenges. The study concludes that while peace-promoting frames are emerging, they remain underutilised. It recommends strategic partnerships between media organisations and peacebuilding bodies to promote conflict-sensitive journalism and enhance the media's role in fostering dialogue, understanding, and reconciliation in Nigeria.KeywordsFarmer-herder conflicts, Framing Theory, conflict reporting, peace advocacy, mainstream media